Changes in molecular integrity of chloroplast DNA and mitochondrial DNA in maize - Kumar, Rachana Ajay (My University, 2015)
Genome copy number is typically two for the nucleus in diploid plants and animals, regardless of developmental or environmental changes, and nuclear DNA is stable. For genomes in mitochondria and chloroplasts, I report that their copies and their DNA integrity change greatly during development in maize. In order to accurately determine organellar genome number, I devise new experimental procedures to overcome limitations of the standard PCR-based methods. First, I describe a new experimental procedure to avoid the confusing influence of nuclear-located organellar DNA (orgDNA) sequences on authentic orgDNA using the PCR. The procedure includes designing organelle-specific primers using bioinformatics methods and methylation-sensitive PCR. In addition to copy number determination, this procedure should be useful in a wide range of applications, including phylogenetic and functional analyses, as well as in a clinical setting. Further, I devise a novel long-PCR method to quantify DNA damage, molecular integrity, copy number, and amount of repair for both plastid DNA and mitochondrial DNA during maize leaf development. I find a developmental increase in orgDNA damage and molecules with impediments that prevent amplification by Taq polymerase, with light causing the greatest change. I also find a hundred- to a thousand-fold decrease in functional copies of orgDNA during leaf development. I suggest that the changes in molecular integrity of orgDNA during development are due to oxidative stress from energy metabolism that damages orgDNA. As leaves develop, the maintenance of high-copy orgDNA lessens, damage persists, and orgDNA is degraded. Furthermore, I confirm a hypothesis that oxidative stress causes DNA damage by studying differences in orgDNA between mesophyll and bundle sheath cells. Higher ROS levels occur in mesophyll due to the light-dependent reactions of photosynthesis. When compared to mesophyll cells, bundle sheath cells have less orgDNA damage and a higher percentage of unimpeded orgDNA. In addition, the orgDNA is more fragmented in mesophyll than bundle sheath cells. The data indicate that higher levels of ROS in mesophyll than bundle sheath cause orgDNA damage. The similar trend in orgDNA properties (copies, damage, and repair) for both plastid DNA and mitochondrial DNA suggests inter-organellar signaling and common regulation by nuclear genes.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Chloroplast DNA; DNA repair; Maize; Mitochondrial DNA; Polymerase Chain Reaction; Reactive Oxygen Species; Plant biology; Molecular biology; biology